The effect of a varnish with fluoride on the hardness of the exposed human dentine tissue. - (:unkn) unknown (My University, 1997)
The aim of this study was to evaluate the effect of a new varnish with fluoride, Fluoridin N-5, on the exposed dentine tissue in situ. Human incisors which were mounted into intra-oral devices were worn by six volunteers and the test materials were applied three times a day for fourteen days. Three different materials were used as three test groups: Novalite, Fluoridin gel N-5 and Amalgam liner. Although both the control and test groups showed some increases in hardness, the mean hardness increase of all of the test groups was significantly higher than that of the control group (p = 0.007). However, the comparison of mean increases in hardness values showed no significant difference among the test groups.